Frost periods and frost-free periods in Poland and neighbouringcountries - Tomczyk Arkadiusz M.; Szyga-Pluta Katarzyna; Majkowska Agnieszka (Open Geosciences, 2015)
The main objective of this article is to analysethe multiannual variability of frost occurrence and thelength of the frost-free period in Poland and neighbouringcountries between 1971 and 2010. A frost day was de-fined as a day onwhich the minimum temperaturewas below0°C and the maximum temperature was above 0°C.On average, between March and November, there were 30frost days in Poland and neighbouring countries, and theirnumber ranged between 12 and 61. In the analysed multiannualperiod, there was a statistically significant tendencyfor the last spring frost to be earlier. Conversely,the first autumn frost occurred increasingly late, althoughthe changes were not statistically significant. All but threestations (Augsburg, Kaliningrad, Olsztyn) recorded an increasein the length of frost-free periods, which was statisticallysignificant in 51% of stations. The pressure conditionconducive to the occurrence of frosts was anticycloniccirculation, as confirmed by the SLP and z500 hPa mapswhich were drawn up, and the Grosswetterlagen (GWL)classification types which were distinguished.